Odpowiedzi

2009-10-09T14:34:18+02:00
3/4x + 1,8 = 1/3
3/4x = 1/3 - 1 cala i 2/5
3/4x = 1/3 - 7/5
3/4x = 5/15 - 21/15
3/4x = - 6/15 /:3/4
x = - 6/15 * 4/3
x = - 8/15

1-3x/2 = 5x+4/3 / * 6
3(1-3x) = 2(5x + 4)
3 - 9x = 10x + 8
-9x - 10x = 8-3
-19x = 5 /:(-19)
x= - 5/19

0,8 - 0,5x/4 = 1,2 + 3/3 / *12
3(0,8-0,5x) = 4(1,2+3)
2,4 - 1,5x = 4,8 + 12
-1,5x = 16,8 - 2,4
-1,5x = 14,4 / (-1,5)
x= - 9,6

jest na 100% dobrze!
1 5 1
2009-10-09T16:19:12+02:00
3/4x+1,8=1/3
3/4x+18/10=1/3
3/4x=1/3-18/10
3/410/30-54/30
3/4x=-44/30
x=-44/30÷3/4
x=-44/30*4/3
x=-176/90
3/4*(-176/90)+1,8=-44/30+1,8=-44/30+18/10=-44/30+54/30=10/30=1/3

1-3x 5x+4
____=__________
2 3

1-3x (5x+4)
____ - _________=0
2 3

3-9x (10x+8)
____ - _________=0
6 6

3-9x-10x-8
___________________=0
6

-5-19x
____________=0
6

-5-19x=0
-19x=5
x=-5/19

1-3*(-5/19) 1+15/19 19/19+15/19
____________=____________=______________=
2 2 2

=34/19*1/2=34/38=0,89


5*(-5/19)+4 -25/19+76/19
_________________=____________ = 51/19*1/3=51/57=0,89
3 3


0,8-1/2x 1,2+3
____________=__________
4 3
0,8-1/2x (1,2+3)
________________-_____________=0
4 3

8/10-1/2x 12/10+3
___________________-________________=0
4 3
3*(8/10-1/2x) 4*(12/10+3)
___________________-_______________=0
12 12

2,4-1,5x-(4,8+12)
______________________=0
12


2,4-1,5x-4,8-12=0
-1,5x=12+4,8-2,4
-1,5x=14,4
x=-9,6

0,8-1/2x 0,8-1/2*(-9,6) 0,8+4,8
_______________=____________= __________=1,4
4 4 4


1,2+3
____________=4,2÷3=1,4
3